THE EFFECT OF COLLABORATIVE TEACHING TECHNIQUE AND STUDENT’S PERSONALITIES ON STUDENTS’ ACHIEVEMENT ON HORTATORY EXPOSITION WRITING - Christina N Saragi; Lastri Wahyuni Manurung; Dewi Paulina Silalahi; Yohana Friscila Naibahao (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2024)
This research aimed to observe whether the writing scores of hortatory texts for extroverted students are higher when compared to introverted students who use collaborative techniques. Quantitative methodology was used in this research and the population included 60 students. 49 students were selected as samples, each from the extrovert group of 28 students and the introvert group of 21 students, both groups were distanced using collaborative techniques. According to data analysis, the extrovert students' hortatory exposition writing scores taught using collaborative techniques were higher than the extrovert students' hortatory exposition writing scores taught using collaborative writing teaching techniques. The writing instrument is in the form of a horatory exposition writing test, while to determine whether a student's personality is classified as extrovert or introvert, a valid questionnaire is used.